An Unusual Presentation of Mycotic Popliteal Artery Pseudoaneurysm due to Pasteurella multocida Infection - Orgiu, Antoni; Zanier, Thomas; Kashi-Dakhil, Mahine; Zaimi, Rym; Dakhil, Bassel; Longuet, Pascale; Bagan, Patrick (International Journal of Angiology, 2020)
Pasteurella multocida, a zoonotic infectious pathogen, is a rare cause of mycotic aneurysms in human hosts. A 76-year-old man was admitted at our emergency unit for a superinfection of his right limb. The patient was initially treated for a knee arthritis. After a first-line antibiotherapy, the patient was referred to the vascular department for the management of a right acute limb ischemia. The work-up revealed a ruptured pseudoaneurysm of the popliteal artery. The ruptured artery was surgically explanted, and a femoropopliteal bypass was then performed. Pasteurella multocida was detected after bacterial analysis of the aneurysm. The postoperative course was uneventful. This case is the first reported case, to our knowledge, of a popliteal artery pseudoaneurysm due to Pasteurella multocida infection.
Keywords: Pasteurella multocida; popliteal pseudoaneurysm; mycotic pseudoaneurysm